A Study on Speaking Skill Difficulties Encountered by the Eleventh-Grade Students of the Islamic Boarding School of Darul Aman Gombara - Rahmayanti, Fadilah; Sulaiman, Iskandar; Halim, Abdul (Har Press Indonesia, 2024)
This research aims to find the students' speaking skill difficulties, the causes of students' difficulties and to know the teacher strategies for overcoming the speaking difficulties encountered by the eleventh-grade students of the Islamic boarding school of Darul Aman Gombara Makassar. The research design of this research is descriptive qualitative. The data were collected through classroom observation and interviews. The findings indicate that (1) The students' speaking skill difficulties encountered by the Islamic Boarding School Darul Aman Gombara students were classified into two aspects; linguistic and non-linguistic problems. The linguistic problems are divided into three kinds; lack of vocabulary, incorrect pronunciation, and lack of grammatical knowledge. Nonlinguistic Problem is divided into Fear of Making Mistakes, shyness, and anxiety. (2) There are some causes of the students' speaking skill difficulties encountered by the Islamic boarding school of Darul Aman Gombara students. Those problems were caused by several problems such as; insufficient subject knowledge, low motivation, limited practice, and English being difficult to learn. (3) and some strategies used by the teacher in overcoming students' speaking skill difficulties were; Games, Role Play, Storytelling, and Brainstorming.